The Concept of Answerability in Mikhail Bakhtin’s Moral Philosophy - Apressyan, Ruben (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
In Mikhail Bakhtin’s moral philosophy, answerability (responsibility) is an integral characteristic of the act, along with eventness, participation, emotional-volitional tone, self-awareness, and the personality’s orientation toward the Other. Answerability synthesizes all these characteristics of the act and can be justifiably perceived as a holistic representation of the act, and of morality in general, since Bakhtin constructed his moral philosophy as a philosophy of the act, and the act was viewed as the holistic embodiment of morality. The article examines two images of answerability that emerge in Bakhtin’s early works. On the one hand, answerability in his understanding is concrete and unrepeatable, carried out from “unique place in being’ in relation to this being, and in this sense it is Self-centred. On the other hand, Bakhtin’s recognition of the complex architectonic of the act, determined by the value attitudes “I-for-myself, the other-for-me, and I-for-the-other,” opens up a perspective on answerability in which it appears as a response not to being, even in the concreteness of the Being-as-event, but to the Other as a participant in it, as the Other in general. In the concept of answerability as presented in the treatise, Toward a Philosophy of the Act, there is a semantic dynamic characteristic of Bakhtin’s early philosophical work (unreflected upon by him in the texts themselves) – from monologism to dialogism, from a philosophy of the act to a philosophy of dialogue, the actual consequences of which are revealed in the thinker’s mature works.